Development and validation of a scale as a tool for improving happiness in the classroom - Cerdá Suárez, Luis Manuel (10th International Conference on Education and New Learning Technologies (EDULEARN), 2021)
The growth of the virtual learning at universities over the past decade is one of the most widely used examples to understand how the recent evolution of computing in all manner of devices has caused the creation of the Digital Education, which in turn demands changes in teaching practice and theory. For this reason, the effectiveness of didactic strategies in the classroom requires the ability to analyze and measure the most relevant attributes in virtual teaching environments in order to improve the happiness and satisfaction of the students in the classroom. The importance of this paper is focused to appreciate the implications of happiness in the classroom as a tool for improving educational processes at universities. The experience of the diverse didactic techniques and methodologies is important for designing the academic and professional curriculum of the pupils, and of course it can be of relevance to leaders of educational institutions and teachers for the improvement of their own pedagogical performance. Systematic, accurate and timely indicators are critical for an educational institution to assess whether they are achieving their aims, that is, the selected strategy is appropriate to achieve their several pedagogical objectives.
Keywords: teaching style; scale development; happiness; educational processes; university; WOS(2)